Assessing the applicability of the cobweb model's proposition in the career choice trend of selected senior high school students in EVSU and LNHS. - Borbon, Anthea Aivi (Tacloban City Anthea Aivi Borbon [and] Manilyn M. Catuday, 2010)
This study sought to assess the applicability of the Cobweb Model's proposition about the role of supply, wage and demand in choosing a career among selected senior high school students in EVSU and LNHS. This research found out that the factors affecting career choices of the respondents were high wage, high prestige attached to the course, and currently in-demand. Moreover, the three top chosen careers were Accountancy, Nursing, and both Management and Engineering which gathered the same percentage.
Undergraduate thesis (B.A.S.S. Economics)--University of the Philippines, Tacloban
Keywords: Social Science